Initial experience with the PASCAL ace implant system for treatment of severe tricuspid regurgitation - Aurich, Matthias; Volz, Martin J.; Mereles, Derliz; Geis, Nicolas; Frey, Norbert; Konstandin, Mathias; Raake, Philip (Circulation. Cardiovascular interventions, 2021)
Download figureDownload PowerPoint
Gesehen am 15.10.2021